Experimental Measurement on Pebble Flow Discharge in a Hopper Silo Based on a Drainage Method - Liu, Yujia; Peng, Sifan; Gui, Nan; Yang, Xingtuan; Tu, Jiyuan; Jiang, Shengyao (Frontiers in Energy Research, 2021)
The dropping of absorption sphere from the storage vessel under accident conditions and the transportation of spent fuel elements in the reactor will both lead to the pebble flow discharging process driven by gravity in a hopper silo. Therefore, the research on the gravity-driven discharging rate of pebbles in a hopper silo has significant engineering guidance for reactor safety. In general, the idea of falling pebbles weighing to obtain the discharging rate becomes the most common experimental measurement method. However, due to the limitation of response frequency and the disturbance of pebbles falling, the resolution of experimental results is limited, and the uncertainty is introduced into the data error, which is difficult to eliminate. In this experiment, a volume measurement based on drainage method is adopted. The magnetostrictive liquid level sensor is used to measure the rise of liquid level caused by the volume of falling pebbles. The bucket for collecting falling pebbles and the pipe equipped with sensors are connected by the channel to form a connected vessel, which ensures the same liquid level on both sides. The damping device arranged on the measuring liquid surface and in the connecting channel eliminates the liquid level fluctuation caused by the pebble falling. Compared with the weighing method, the accuracy of this method is determined by the sensor accuracy and the cross-sectional area of the connector. Therefore, under the same instrument accuracy, this method can obtain higher measurement accuracy. In terms of resolution, the disturbance caused by the momentum of falling pebbles will not be introduced into this method, and the resolution of less than 20 pebbles can be achieved at a sampling frequency of 100Hz. Based on this method, the effect of silo outlet size on pebble discharge flow rate fluctuation have been also analyzed in this study